Financiamiento de Generadoras Eléctricas de Energía Renovable en Perú - Soriano Castillo, Gonzalo (2020)
In Peru, as part of a global trend, for more than a decade the development of renewable energy generators has been promoted from the State under the signing of RER contracts. In this article we will delve into the financing methodology to which this type of project has access, establishing its main characteristics and problems.